2013
DOI: 10.1002/j.2205-0140.2013.tb00247.x
|View full text |Cite
|
Sign up to set email alerts
|

Malposition of Double Lumen Bicaval Venovenous Extracorporeal Membrane Oxygenation (VV ECMO) cannula resulting in hepatic venous congestion

Abstract: Introduction: Optimal positioning of double lumen bicaval canula for extracorporeal membrane oxygenation (ECMO) support used as a rescue measure in refractory hypoxaemia is essential to facilitate adequate oxygenation, prevent recirculation and avoid complications. Method: Echocardiography via transoesophageal or transthoracic windows can be used as guidance and as a surveillance technique to prevent cannula malposition. We describe a case of Double‐Lumen Bicaval VV ECMO cannula malposition leading to a massiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Cannula malposition was identified early using TTE, and appropriate repositioning of the cannula was undertaken, thus saving the patient from the likelihood of developing a massive degree of retrograde flow into the hepatic veins with the potential to cause severe hepatic venous congestion, hepatic insufficiency, severe portal hypertension, and capsular distention and rupture. 12 Even though TEE may provide superior spatial resolution for the visualization of ECMO cannulae, this case demonstrates that TTE still can play an important role in the management of the patient requiring ECMO support. Because cannula malposition can lead to rapid clinical deterioration with potentially fatal consequences, the use of a noninvasive, focused TTE examination to quickly and easily identify and correct cannula malposition is obvious.…”
Section: Discussionmentioning
confidence: 93%
“…Cannula malposition was identified early using TTE, and appropriate repositioning of the cannula was undertaken, thus saving the patient from the likelihood of developing a massive degree of retrograde flow into the hepatic veins with the potential to cause severe hepatic venous congestion, hepatic insufficiency, severe portal hypertension, and capsular distention and rupture. 12 Even though TEE may provide superior spatial resolution for the visualization of ECMO cannulae, this case demonstrates that TTE still can play an important role in the management of the patient requiring ECMO support. Because cannula malposition can lead to rapid clinical deterioration with potentially fatal consequences, the use of a noninvasive, focused TTE examination to quickly and easily identify and correct cannula malposition is obvious.…”
Section: Discussionmentioning
confidence: 93%
“… 13 Several case reports have described the use of transthoracic echocardiography (TTE) to interrogate a pVV-ECMO cannula creating a congestive hepatopathy, which resulted in the correction of hepatic venous obstruction and retrograde hepatic venous flow. 7 , 8 Hepatic ultrasound evaluation, with portal spectral Doppler interrogation, is vital to the workup of a hepatic injury. Figure 4 illustrates basic hepatic anatomy, while Figure 5 further characterizes this anatomy and depicts probe placement for ultrasound image acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…A rarely reported complication of ECMO therapy involves hepatic congestion due to aberrant cannula placement. 7 , 8 Herein, we report a case of acute hepatic decompensation in a patient receiving centralized venovenous ECMO (VV-ECMO) therapy and describe the further characterization of this phenomenon through interrogation of hepatic venous spectral Doppler flow rate. The patient’s family provided permission for the publication of this report.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study demonstrated up to 38% of patients requiring echo-guided cannula adjustment after initial successful cannula positioning,14 Avalon cannula dislocation can be classified into longitudinal and rotational. In case of longitudinal dislocation, the cannula tip may be advanced too deeply and cause hepatic congestion, either directly by cannula threading into the hepatic vein, or indirectly by retrograde flow emanating from the middle port 13 15 16. On the contrary, the cannula tip may be too shallow in the right atrium and impacts the surrounding structures, such as right coronary artery compression, coronary sinus insertion or is deviated into the right ventricle and causes tricuspid injuries and even right ventricular perforation 8 11 17.…”
Section: Discussionmentioning
confidence: 99%